2020
DOI: 10.1111/echo.14825
|View full text |Cite
|
Sign up to set email alerts
|

The utility of bedside echocardiography in critically ill COVID‐19 patients: Early observational findings from three Northern New Jersey hospitals

Abstract: Introduction Cardiovascular complications related to coronavirus disease 2019 (COVID‐19) have led to the need for echocardiographic services during the pandemic. The present study aimed to identify the echocardiographic findings in hospitalized COVID‐19 patients and their utility in disease management. Methods We included patients who were diagnosed with COVID‐19 using polymerase chain reaction and those who underwent echocardiographic examination during their hospitalization. Results Altogether, 45 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Szekely et al ( 5 ) showed that RV dysfunction was more common in patients with elevated troponin levels and a poor clinical grade, whereas the total number of patients with an impaired LV function was relatively smaller. Notably, in several other studies, LV dysfunction was not rare in patients with COVID-19 ( 18 , 23 , 25 ). This discrepancy among studies may be due to differences in the study populations, but RV damage is still universally found by echocardiography in patients with COVID-19.…”
Section: Rv Involvement From Cardiac Images In Patients With Covid-19mentioning
confidence: 67%
See 3 more Smart Citations
“…Szekely et al ( 5 ) showed that RV dysfunction was more common in patients with elevated troponin levels and a poor clinical grade, whereas the total number of patients with an impaired LV function was relatively smaller. Notably, in several other studies, LV dysfunction was not rare in patients with COVID-19 ( 18 , 23 , 25 ). This discrepancy among studies may be due to differences in the study populations, but RV damage is still universally found by echocardiography in patients with COVID-19.…”
Section: Rv Involvement From Cardiac Images In Patients With Covid-19mentioning
confidence: 67%
“…We summarized the results of recent cardiac imaging studies ( Table 2 ). Among patients with COVID-19-related myocardial injury, the proportion of RV dilatation ranged from 13.3 to 48.9% ( 5 , 6 , 17 , 20 , 23 ). RV dilatation associated with elevated D-dimer levels and C-reactive protein levels was more common in patients with COVID-19 ( 6 , 17 , 18 , 20 ).…”
Section: Rv Involvement From Cardiac Images In Patients With Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is infrequently performed due to the invasive nature of the procedure and the probability of sampling errors caused by the characteristic patchy inflammation [ 2 , 10 ]. The more commonly performed studies include ECG, echocardiography, cardiac magnetic resonance imaging (CMRI) [ 11 ]. Markers of inflammation, viral serology, and cardiac biomarkers that include troponins and creatine kinase may also help confirm the diagnosis [ 1 , 9 ].…”
Section: Discussionmentioning
confidence: 99%